(untitled) (Praxis Educativa, 2012)
The commitment with La Pampa’s social needs as a constituent of the teacher’s role, was taken on by the AMP (La Pampa Teachers’ Association). The AMP reflected the average conscience of La Pampa school teachers about the inherent spirit in their job. To exercise this and other postulates, such as the defense of the public school and laicism, the AMP had to face an adverse Ideological atmosphere. This atmosphere and its repressive practices - in charge of the CNE (National Council of Education) - could be identified broadly with the height of the restorative nationalism emergent in the 1930 coup d’état, and its continuity in the catholic nationalism that supported the 1943 coup d’état Between these two events, the confrontation CNE - AMP is analyzed from the point of view of emblematic cases, over which intellectual links can be built. These links connect past events among themselves and with the present from an ideological universe identified with the dialectical fertility of the conflict.